2018
DOI: 10.1038/s41598-018-33783-3
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors for success in renal denervation–a single centre retrospective analysis

Abstract: Renal denervation (RDN) is one of the most frequently used invasive methods for the treatment of arterial hypertension. However, recent randomized sham-controlled studies raised concern about the efficacy and predictability of response. We retrospectively analyzed outcomes of patients, who underwent RDN in our hypertension center between November 2010 and April 2014 and report here outcomes twelve months after procedure based on 24-hours ambulatory blood pressure monitoring. We defined ten-mm Hg decrease in of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…The study did not involve blind randomization for the use of a particular type of catheter; patients were included in the groups as the catheters were modifi ed. In this study by analogy with previously published studies (13) the patients in whom BP reduction of 10 mmHg or more was achieved were considered as responders.…”
Section: Methodsmentioning
confidence: 99%
“…The study did not involve blind randomization for the use of a particular type of catheter; patients were included in the groups as the catheters were modifi ed. In this study by analogy with previously published studies (13) the patients in whom BP reduction of 10 mmHg or more was achieved were considered as responders.…”
Section: Methodsmentioning
confidence: 99%
“…Response to RDN was defined as a ≥10 mm Hg reduction in office systolic BP or ≥5 mm Hg reduction in 24‐hours ambulatory systolic BP, as used in previous studies 9,23‐25 . Major adverse events were defined as safety endpoints, and it was reported whether they were related to study intervention.…”
Section: Methodsmentioning
confidence: 99%
“…For a post hoc sample size evaluation, a clinically relevant difference of ≥10 mm Hg in office systolic BP was assumed 9,23‐26 . For the power analysis, we used a simulation‐based approach with 1000 simulations on the mixed model with dependent variable office systolic BP over time and independent variables time‐point (1, 6, 12, 24, and 36 months), including random patient intercepts.…”
Section: Methodsmentioning
confidence: 99%
“…3 The significant reduction in BP may be related with the placebo effect or with the increased baseline BP prior to procedure. 26 The changes in patient seletion and technique, and the results of recent randomized trials bring new perspectives into the treatment of RH, whose pressure control is inadequate, despite all the available drug armamentarium. The most robust randomized trials have already shown the biological validity and clinical utility of RSD.…”
Section: Post Symplicity Htn-3 Studiesmentioning
confidence: 99%